KETIMPANGAN PENDIDIKAN ANTAR KABUPATEN/KOTA DAN IMPLIKASINYA DI PROVINSI JAWA TENGAH - Muhammad Ja'far Bustomi (Economics Development Analysis Journal, 2012)
This study aims to analyze the educational disparities among districts / cities and find out what factors affect educational inequality, the influence of educational inequality with GDP growth per capita in the province of Central Java. Data analysis method used in this study is education Gini index, with panel data regression analysis techniques Pooled EGLS. Based on the analysis of educational inequality between districts / cities and its implications in the province of Central Java is known that the calculation of Gini index of education in the province of Central Java is included in the category of low educational inequality (0.309), with contributors educational inequality is the inequality of education in districts and cities. In the first regression model it is known that the independent variable of government spending on education, and life expectancy negative effect on educational inequality significantly. While the gender gap variable is significantly positive effect on the dependent variable educational inequality. Variables that did not significantly influence educational inequality is the variable of income inequality. In the second regression model in mind that educational inequality has a significant negative effect on the growth of GDP per capita in the province of Central Java.